Hybridisation in European ungulates: an overview of the current status, causes, and consequences. (17th October 2018) - Iacolina, Laura; Corlatti, Luca; Buzan, Elena; Safner, Toni; Šprem, Nikica
Abstract: Hybridisation and gene introgression are important sources of diversification, the relevance of which in the evolutionary processes is well recognised. Their fitness consequences in animal populations, however, are not sufficiently well understood, despite hybridisation rates becoming increasingly important worldwide following human‐related activities such as domestication, game management and habitat alteration. In Europe, the density and distribution of native ungulates have largely been influenced by humans since pre‐historic times. This, alongside the introduction of non‐native and domesticated species, may bear major consequences at the genetic and population levels. We provide an updated overview of recent hybridisation events in wild European ungulates; we describe their ecological drivers, extent, current distribution, potential consequences and proposed management strategies. We reviewed the scientific literature published between 2000 and 2018 and found that confirmed hybridisation was described in 75 of the 89 references we included, involving nearly all the species that we investigated. Most researchers relied on genetic information for hybrid identification, which often involved a domestic counterpart. However, introductions and translocations also led to crossbreeding between wild ungulate (sub)species. Only 43 papers provided management recommendations, mostly focused on preventing hybridisation and removing hybrids. Hybridisation proved to be relatively common in several ungulate taxa in Europe. Despite reported changes in phenotype and fitness‐related traits in some species, the consequences of hybridisation for adaptation, life history, and evolutionary potential remain largely unknown. The current conservation paradigm aims to prevent the spread of domestic or non‐native genes in native populations; accordingly, conservation plans should: 1) determine the genetic origin of possible source populations; 2) protect native populations from the risk of crossbreeding with non‐native ones, and 3) establish permanent monitoring.